PERAN BANK SAMPAH LESTARI TERHADAP LINGKUNGANNYA DI RW 01, CIPADU, LARANGAN, KOTA TANGERANG - Munawir, Munawir; Rangkuti, Zulkifli; Irawaty, Rosalia (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
The Lestari Garbage Bank (BSL) located in RW 01 Cipadu, Larangan, Tangerang City, was established on November 11 2014, with 22 customers as members. The Lestari Garbage Bank (BSL) has performed its function as a waste bank, namely sorting, depositing, weighing, calculating, profit sharing and has other benefits for customers and their management. The Lestari Garbage Bank (BSL), has carried out socialization on environmental control, waste handling through waste banks so that R3 (Reuse, Reuse and Recycle) can be carried out and benefits / income / money can be obtained. The last garbage weighing was on May 27 2023 (3 weighings, once every 2 weeks) the result was Rp. 1,982,850, -, after deducting the 30% BSL operational costs, a net result of Rp. 1,387,995, - which was distributed to customers who deposited trash, for RT 06/01 they received Rp. 650,000, -, while the rest is for others.The existence of the Lestari Garbage Bank (BSL) has been recognized in the RW 01 area and its surroundings, but the increase has not yet shown a real increase. Because of this, more persistent efforts are needed to make the community aware so that they can participate more actively to become customer members of the Sustainable Garbage Bank (BSL).